Assessment of the ability, perception, and readiness of nurses to manage tracheostomy-related complications in Riyadh City: a cross-sectional study - Fahad Zarraq Alotaibi; Reema Alkhatabi; Lujain Allowaihiq; Hassan Alhazzani; Ghada Alshehri; Eman A. Hajr; Feras Alkholaiwi (BMC, 2022)
Abstract Background Nursing staff play a key role in the bedside management of tracheostomized patients in both intensive care units and general floors. Effective provision of postoperative care to these patients by nurses is critical. This study aimed to assess the readiness of nursing staff to manage tracheostomy-related complications in Riyadh, Saudi Arabia. Methods This cross-sectional study enrolled 395 nurses in Riyadh, Saudi Arabia. A self-administered questionnaire developed by the authors was distributed to nurses via an online survey. The questionnaire assessed nurses' socio-demographic characteristics and their knowledge and practices regarding tracheostomy indications, postoperative care, and management of its complications. Results Of respondents, approximately 59% (232/395) had poor knowledge regarding tracheostomy-related complications and indications, 39% (154/395) had moderate knowledge, and only 2%(9/395) had good knowledge. Several factors were associated with increased knowledge, including having a higher education degree, working in a tertiary/quaternary hospital, being a government employee, caring for tracheostomized patients, and attending courses or lectures on managing tracheostomized patients. Conclusions Knowledge level and practices regarding tracheostomy-related complications and indications among nurses remain limited. In-service continuous professional development programs for nurses working in all hospital settings are strongly recommended. Further research is warranted to elicit the major factors contributing to inadequate knowledge and practices among nurses in Riyadh.